The Self-Organizing City and the Architecture of Metabolism: An Architectural Critique on Urban Growth and Reorganization - Eken, Cemaliye; Atun, Resmiye Alpar (Mdpi, 2019)
Over decades, cities have undergone rapid urbanization and uncontrolled urban growth. The need for future cities to operate as adaptable complex systems has generated an interest in the self-organizing resilient city. The main aim of the study is to find ways of conceptualizing self-organizing the resilient city as an emerging field of research for urban design and architectural theory. Based on these assumptions, an integrated relationship between architecture and urban design are seen as potential catalysts for absorbing the uncertainty and disturbances of urban growth and preparing the structure, function, and identity of a city as a self-organizing system that can continuously and freely adapt to changes. The paper seeks to determine the role of architecture in urban design as a main key for facilitating a self-organizing system. A systematic theoretical research method was used to describe resilience theory and self-organizing systems within an adaptive cycle and hierarchical thinking across scales. The study then sought to identify the earliest point that architectural theory conceptualized future cities from the perspective of self-organizing systems. The Metabolism movement was chosen to provide a basis for the discussion of the study. Cities as self-organizing systems need to be considered through cross-scale interactions. For a self-organizing resilient city, the inter-reliance between architecture and urban design drive the main inputs to the system.
Keywords: resilience; self-organizing city; adaptive cycle; cross-scale interactions; urban growth; renewal; metabolism movement; urban space; architecture